ANALISIS KARAKTERISTIK PEKERJAAN, STRES KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA ASN PADA DINAS PERTANIAN DAN PERIKANAN KABUPATEN PONOROGO - Windiyastutik, Arida Tri; Rispantyo, Rispantyo; Widajanti, Erni (Universitas Slamet Riyadi, 2020)
The study was conducted at the Department of Agriculture and Fisheries of Ponorogo Regency, the types of data used were qualitative and quantitative. Data sources used are primary and secondary data. With the survey method with a population of 291 people. The sample method uses a purposive sampling method that is structural ASN and a total of 94 people is obtained. Data analysis technique used multiple regression analysis which was previously tested for validity and reliability of the questionnaire. In this study shows that job characteristics and job satisfaction do not significantly influence performance. Job stress has a significant effect on performance.